Dance psychology : the science of dance and dancers - Lovatt, Peter (Psychologist) (Norfolk, UK : Dr. Dance Presents, 2018)
"Dance Psychology is the study of dance and dancers from a scientific, psychological, perspective. This Dance Psychology textbook provides a general introduction to the Psychology of Dance and then it delves in to eleven of the most central questions concerning Dance Psychology. Are humans born to dance? Does the way you move your body change the way you think? Will dancing make people happier? Can dancing put people in to a trance-like state? Will a person's dance confidence change across the lifespan? Does dancing make people healthier? Why do we enjoy watching some dance performances more than others? How do dancers remember so many dance routines? Why don't dancers get dizzy? Will dancing improve a person's self-esteem? How do we communicate emotions with our body? Drawing on academic literature, this book is engaging, technical and, in places, critical; it is essential reading for anyone with an interest in Dance Psychology."--Page 4 cover.
P.B
P.B
Includes bibliographical references.
Keywords: Dance -- Psychological aspects; Danse -- Aspect psychologique; Dance -- Psychological aspects; Dans; Psychologische aspecten